Modelo y estrategias para el desarrollo turístico post terremoto en Manabí. - Barreiro Intriago, Karla Cecilia (2018)
The objective of this research was to design a model and strategies with the purpose of making contributions that contribute to the post-earthquake tourist development in Manabí. The type of research adopted was mixed with a descriptive approach in which four phases were proposed for the implementation of the same, beginning with the tourist diagnosis that through various instruments allowed to determine that despite the earthquake of 16 A Manabí, as a family destination and nature, meets the necessary and basic conditions concerning the elements of the tourism system with certain deficiencies, where the problems lie in the incipient planning and management. In the second phase, tourism management was analyzed, where it was identified that each public and private actor has a specific function, however, they do not have much participation in development due to the disarticulation between actors, low budget, lack of training and specialization, among other. In the third stage, as part of the proposal, a planning based on the previous results was structured, comprising the strategic formulation with 2 objectives, 6 lines of action, with 10 programs and projects respectively, aiming to solve the problems detected. Finally, the fourth phase corresponded to the formulation of the tourism model that took as a basic strategy the planning formulated linking public management articulated in turn with private and community actors, in a governance process. This involved the setting of indicators for the measurement and evaluation of development Manabí.